Levels of Heavy Metals in Soil, Water and Vegetables around Industrial area in Bauchi, Northeastern Nigeria - B.A. Sulaiman; MB Sulaiman; A. Ahmed; I.A. Maigari; A.F. Tijjani (Journal of Applied Sciences and Environmental Management, 2021)
This study examined the levels of heavy metals in soil, water, and vegetables (amaranthus, hibiscussabdariffa, and allium cepa leaves) around the industrial area Bauchi, Northeastern Nigeria. The composite samples of soil, water, and vegetables were collected and determine the level of heavy metals (Mn, Zn, Cd, Pb, and As) using Atomic Absorption Spectrophotometer (AAS). The level of the heavy metals decreased in the order of Mn > Zn > Pb > Cd, Pb > Zn > Mn > Cd, and Mn > Zn > Mn > Cd in the soil, water, and vegetables respectively. Among the vegetables, amaranthus had the highest heavy metals level followed by allium cepa leaves and hibiscus sabdariffa. The levels of heavy metals obtained were below the tolerance level recommended by the world health organization (WHO). The bio-concentration factors of the heavy metals for the studied samples were below one except Zn in amaranthus. The daily intake of metals for Mn was found to be the highest in amaranthus for children and estimated to be 1.149 mg/person/day. Health risk index of Zn for amaranthus and allium cepa leaves for children and Pb for amaranthus, hibiscus sabdariffa and allium cepa leaves for both children and adults were above 1, except in hibiscus sabdariffa for adults, signifying provable of health risks for the consumption of the vegetables in the study area. Therefore, the consumption of these vegetables as food could pose a health hazard, and regular monitoring is recommended to prevent metal accumulation with their associated health implications in the consuming public.